Technology and parenting in the digital age: opportunities and risks (2021)
In the 21st century, digital technologies have become an integral part of children's lives. Child-rearing practices have become more complicated in recent years as digital media have become more common and pervasive in everyday life, even in the modern home. Parents are now caught between two worlds: on the one hand, they encourage their children to use digital media for educational and social purposes, and on the other hand, they are concerned about their children's safety online. They, however, strive to reduce the risks and limit the negative consequences of their children's use of digital media. Based on these, this paper examines digital technology, digital parenting, opportunities and risks, and how parents can employ a variety of techniques to regulate their children's digital media activities, such as setting limits, setting up internet filters to block unsuitable websites and content for child(ren), spending time with their child(ren), and so on. It recommended that parents and children alike should have adequate digital literacy skills. This is one of the most important prerequisites for safe internet use, thus, promoting a safe and healthy online environment for them and their children